ADMINISTRATION OF RED DRAGON FRUIT TO PREGNANT WOMEN IN TRIMESTER III ON INDICATIONS OF MILD ANEMIA AT GEYER 1 PUSKESMAS - Galuh Chaurullisa; Nurya Kumalasari (The Shine Cahaya Dunia Kebidanan, 2022)
Background: Pregnancy according to the International Federation of Obstetrics and Gynecology, pregnancy is defined as fertilization or union of spermatozoa and ovum and continued with nidation or implantation. Anemia of pregnant women is a maternal condition where the hemoglobin level is below 11 g/dl, anemia that often occurs in pregnant women is anemia due to iron (Fe) deficiency (Sulistyoningsih, 2012). The purpose of the study was to provide obstetric care with a focus on giving dragon fruit interventions to help increase hemoglobin in third trimester pregnant women. Method: The research design that the researcher uses is a case study research design. This type of descriptive case study research uses participatory observation method. The subjects in this study were pregnant women in the third trimester Results: The results showed that Mrs. Y had mild anemia and the mother complained that she was often weak. Evaluation of the implementation of the intervention by giving dragon fruit 100 g/day. Mrs. Y is no longer anemic Conclusion: The problem of anemia in Mrs. Y 30 weeks pregnant has been resolved